The potential for interstate high-tech oil and gas cluster formation in the Caspian region - A. A. Khachaturyan; N. V. Lyasnikov; A. S. Abdulkadyrov; S. V. Zubkova (Модернизация, инновация, развитие)
Purpose: is to substantiate strategic orientations and mechanisms for the formation of an interstate cluster in the Caspian region based on the comprehensive assessment of the potential of the territories.   Methods: the assessment of five 5 components of the potential of the Caspian littoral states was carried out: economic, scientific and technological, human, infrastructural and investment based on the use of the data normalization method. This made it possible to conduct the comparative analysis and calculate integral indices of the socio-economic development indicators.   Results: the interrelation between the components of the socio-economic potential of the Caspian littoral states has been established, which creates the basis for determining the priority directions for the development of interstate cooperation within the framework of the creation of an oil and gas high-tech cluster. Based on the comparative analysis, the differences in the levels of scientific and technological development of the states of the Caspian region are identified and shown. The study proposed a three-level classification of the Caspian littoral states based on their scientific and technological potential. As a result of the revealed imbalance between the accumulated potential of socio-economic development and the level of development of high-tech industries in the states of the Caspian region, the necessity of formation and implementation of state policy measures aimed at the structural transformation of regional economic systems is determined.   Cconclusions and Relevance: the Caspian region has the necessary prerequisites for the formation of a high-tech oil and gas cluster due to the combination of resource base, human capital and the scientific and technological potential. It is proved that the cluster development strategy should be focused not on obtaining high incomes from the raw materials sector, but on creating a system of income transfer to the development of innovative technologies that provide the states of the Caspian region with the leading position in the Eurasian space. For the effective cluster organization, it is necessary to be guided by the principles of the development, creating a unified infrastructure and institutions that promote the development of innovation activity. The key condition is the creation of mechanisms for interstate coordination, including intellectual property management, joint financing of research and promotion of technology transfer.